Residual meta‐iodobenzyl guanidine (MIBG) positivity following therapy for metastatic neuroblastoma: Patient characteristics, imaging, and outcome. Issue 12 (19th August 2021) - Usmani, Nida; Deyell, Rebecca J.; Portwine, Carol; Rafael, Margarida Simao; Moorehead, Paul C.; Shammas, Amer; Vali, Reza; Farfan, Mateo; Vanniyasingam, Thuvaraha; Morgenstern, Daniel A.; Irwin, Meredith S.
Abstract: Background: Meta‐iodobenzylguanidine(MIBG) scans are used to detect neuroblastoma metastatic lesions at diagnosis and during posttreatment surveillance. MIBG positivity following induction chemotherapy correlates with poor outcome; however, there are reports of patients with progression‐free survival despite MIBG positivity at the end of therapy. The factors distinguishing these survivors from patients who progress or relapse are unclear. FDG‐positron‐emission tomography (PET) scans can also detect metastatic lesions at diagnosis; however, their role in posttherapy surveillance is less well studied. Methods: We performed a retrospective analysis of International Neuroblastoma Staging System (INSS) stage 4 patients to identify those with residual MIBG‐avid metastatic lesions on end‐of‐therapy scans without prior progression. Data collected included age, disease sites, histopathology, biomarkers, treatment, imaging studies, and response. Results: Eleven of 265 patients met inclusion criteria. At diagnosis three of 11 patients were classified as intermediate and eight of 11 high risk; nine of 11 had documented marrow involvement. Histologic classification was favorable for four of 10 and MYCN amplification was detected in zero of 11 cases. The median time with persistent MIBG positivity following treatment was 1.5 years. Seven patients had at least one PET scan with low or background activity. Biopsies of three of three MIBG‐avid residual lesions showed differentiation. All patients remain alive with no disease progression at a median of 4.0 years since end of therapy. Conclusion: Persistently MIBG‐avid metastatic lesions in subsets of patients following completion of therapy may not represent active disease that will progress. Further studies are needed to determine whether MYCN status or other biomarkers, and/or PET scans, may help identify patients with residual inactive MIBG lesions who require no further therapy.